Factors Declining Interest in English Language Training for Sermo Tourism Village Community, Kulon Progo Yogyakarta - Nuharani Kurniyati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
This study investigates the elements that contribute to the community's waning interest in English language training conducted by the